The Development of Categorical Perception of Segments and Suprasegments in Mandarin-Speaking Preschoolers - Ma, Junzhou; Zhu, Jiaqiang; Yang, Yuxiao; Chen, Fei (Frontiers in Psychology, 2021)
This study investigated the developmental trajectories of categorical perception (CP) of segments (i.e., stops) and suprasegments (i.e., lexical tones) in an attempt to examine the perceptual development of phonological categories and whether CP of suprasegments develops in parallel with that of segments. Forty-seven Mandarin-speaking monolingual preschoolers aged four to six years old and fourteen adults completed both identification and discrimination tasks of the Tone 1-2 continuum and the /pa/-/pha/ continuum. Results revealed that children could perceive both lexical tones and aspiration of stops in a categorical manner by age four. The boundary position did not depend on age, with children having similar positions to adults regardless of speech continuum types. The boundary width, on the other hand, reached the adult-like level at age six for lexical tones, but not for stops. In addition, the within-category discrimination score did not differ significantly between children and adults for both continua. The between-category discrimination score improved with age and achieved the adult-like level at age five for lexical tones, but still not for stops even at age six. It suggests that the fine-grained perception of phonological categories is a protracted process, and the improvement and varying timeline of the development of segments and suprasegments are discussed in relation to statistical learning of the regularities of speech sounds in ambient language, ongoing maturation of perceptual systems, the memory mechanism underlying perceptual learning, and the intrinsic nature of speech elements.